2019
DOI: 10.1590/2237-6089-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Dependency, mood instability, and inconsequence traits for discriminating borderline personality disorder

Abstract: Introduction Borderline personality disorder (BPD) is one of the most widely studied personality disorders (PDs). It recurrently shows traits of emotional lability, anxiety, separation insecurity, depressiveness, impulsiveness, risk exposure, and hostility, mainly affecting the domains of negative affectivity and antagonism. Objectives To investigate the most discriminant dimensions of the Dimensional Clinical Personality Inventory (Inventário Dimensional Clínico da Personalidade 2 [IDCP-2]) to distinguish pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The strongest correlation between MIQ-T and a pre-existing scale was demonstrated by PAI-BOR, despite having taken only a few items from the PAI-BOR scale when developing MIQ-T. This is consistent with the literature on MI, as MI is known to be a characteristic feature of borderline personality disorder [ 37 , 38 , 39 ] and can be used as one of the discriminant dimensions that differentiates those diagnosed with borderline personality disorder from a community sample and those with other psychiatric disorders [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 73%
“…The strongest correlation between MIQ-T and a pre-existing scale was demonstrated by PAI-BOR, despite having taken only a few items from the PAI-BOR scale when developing MIQ-T. This is consistent with the literature on MI, as MI is known to be a characteristic feature of borderline personality disorder [ 37 , 38 , 39 ] and can be used as one of the discriminant dimensions that differentiates those diagnosed with borderline personality disorder from a community sample and those with other psychiatric disorders [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 73%
“…Although studies have been conducted to investigate the discriminant ability of IDCP-2 for specific conditions (e.g., borderline personality disorder, dependent personality disorder, bipolar disorder; Carvalho & Pianowski, 2019a;2019b;Carvalho, Painwoski, & Gonçalves, 2018), no studies were found investigating its discriminant capacity for people with substance dependence. However, based on the literature (APA, 2013;Bornovalova et al, 2005;Kotov et al, 2017;Moraleda-Barreno, Díaz-Batanero, Pérez-Moreno, Gómez-Bujedo, & Lozano, 2018), it is possible to identify the conceptual relevant IDCP-2 factors for this purpose: Anxious Concern, Hopelessness, Superiority, Dominance, Indifference, Anxiety, Depression, Risk-taking, Deceitfulness, and Impulsivity.…”
Section: Introductionmentioning
confidence: 99%